2009
DOI: 10.1177/0020852308099510
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating financial performance in local government: maximizing the benchmarking value

Abstract: One of the main problems in evaluating financial performance arises in carrying out comparisons between municipalities, as no account is taken of the impact of certain factors of the social and economic environment on the indicators in question. In this study, the concept of financial condition is applied, revealing the influence of such factors, and a methodology is proposed to minimize their effects on the results of the evaluation. The results of applying these to a sample of municipalities in Spain reveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0
25

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(124 citation statements)
references
References 46 publications
1
90
0
25
Order By: Relevance
“…In this case, the unemployment rate has a negative influence on the financial of local governments, as the findings of previous literature and international organizations had shown [3,47,48]. However, our findings represent an advance because they support that the unemployment rate could affect specifically on the financial capacity of local governments to contribute to sustainable development.…”
Section: Rq 2 -Does the Company's Concentration Affect The Financial supporting
confidence: 77%
See 3 more Smart Citations
“…In this case, the unemployment rate has a negative influence on the financial of local governments, as the findings of previous literature and international organizations had shown [3,47,48]. However, our findings represent an advance because they support that the unemployment rate could affect specifically on the financial capacity of local governments to contribute to sustainable development.…”
Section: Rq 2 -Does the Company's Concentration Affect The Financial supporting
confidence: 77%
“…According to the Fiscal Sustainability Report [3], a higher rate of unemployment has a negative influence on the country's production and income received by the different levels of government (central, regional and local). In parallel, the preliminary investigation revealed that the increase in unemployment has adverse effects on social spending [47], indebtedness [6] and government revenues [48]. In addition, due to the economic crisis, in Spain, the unemployment rate has had an uneven behavior between the different economic sectors (agriculture, industry, building and services) (Public State Employment Service-SEPE).…”
Section: Research Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the public sector, only some countries (USA and Spain), use some systems or models to predict and identify the financial crisis (Kloha, 2005a(Kloha, , 2005bCoe, 2008;Zafra-Gómez, López-Hernández, & Hernández-Bastida 2009). However, in most of the cases, distress is calculated with the financial performance primarily assessed through the concept of financial condition (Carmeli 2003;Carmeli 2008;Honadle 2003;Dollery, Crase & Byrnes, 2006;Audit Commission, 2007;Zafra-Gómez et al, 2009). Therefore, the measurement of financial condition is an indispensable way of evaluating the health status of local governments, considering that good financial health represents a prerequisite for convergence towards the objectives of any institution (Cabaleiro et al, 2013).…”
Section: Causesmentioning
confidence: 99%